Perspectives on the Challenges of Christianity and African Traditional Religion throughout the Ages to Contemporary Times - (:unkn) unknown (My University, 2023)
The explosion of knowledge and education, the extension of communication to all corners of the globe and the mixing of disparate cultures and religious groups are just a few of the elements which challenge us in our efforts to grasp the spiritual dimensions of the reality in which we live and to present a relevant view of Jesus’ gospel to a morally and spiritually distracted world. Contemporary Christianity is the constant modification of New Testament religion to attract the unregenerate and carnal Christians, please the flesh, and be relatively acceptable to the world. According to Awolalu, J.O, Dopamu P.A [1], “the introduction of the foreign religions brought many challenges to the growth and expansion of African religion. In fact, some early missionaries predicted an extinction of the religion". African Culture is dynamic, and it cannot die as being canvassed in some quarters because it is a living institution. Christianity and African Traditional Religion (ATR) are two prominent belief systems that have coexisted and interacted in various ways throughout the history of Africa. While both hold significant cultural and spiritual significance for African communities, they also face unique challenges that impact their practice and relevance in contemporary African societies. This paper will explore and discuss different perspectives on the challenges faced by Christianity and African Traditional Religion in Africa, highlighting key issues that arise from their coexistence and interactions.
Keywords: African Research